1978
DOI: 10.1152/jappl.1978.45.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Tracer priming the bicarbonate pool

Abstract: We have described a technique whereby the time necessary to reach an equilibrium enrichment of expired CO2 during a primed-constant infusion of [U-13C]glucose was shortened from 7 to 8 h to 1 hour or less. We applied the theory of the primed-constant infusion technique to the bicarbonate pool, with the "constant infusion" of labeled carbon dioxide originating from oxidation of the infused [13C]glucose rather than from a labeled infusion of bicarbonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
87
0
2

Year Published

1980
1980
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(90 citation statements)
references
References 0 publications
1
87
0
2
Order By: Relevance
“…This is not necessarily true. In studies where 13 C-bicarbonate had been infused in human subjects the percentage of 13 CO 2 reported as recovered varied widely from approximately 50 to almost 100% (Irving et al, 1983;Allsop et al, 1978;Halliday, 1991). Furthermore, there is evidence to suggest that feeding or underfeeding could affect the amount of 13 CO 2 recovered (Wenham et al, 1991) in labelled experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not necessarily true. In studies where 13 C-bicarbonate had been infused in human subjects the percentage of 13 CO 2 reported as recovered varied widely from approximately 50 to almost 100% (Irving et al, 1983;Allsop et al, 1978;Halliday, 1991). Furthermore, there is evidence to suggest that feeding or underfeeding could affect the amount of 13 CO 2 recovered (Wenham et al, 1991) in labelled experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence to suggest that feeding or underfeeding could affect the amount of 13 CO 2 recovered (Wenham et al, 1991) in labelled experiments. The bicarbonate correction factor has been used to account for this discrepancy (Allsop et al, 1978). More recently, Sidossis et al (1995) suggested that the use of the bicarbonate correction factor is invalid because it does not account for labelled ®xation, which occurs in many tissues through tricarboxylic acid cycle (TCA) exchange reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental protocol was approved by the Institutional Ethical Committee. (4,19). After 2 h ofisotope equilibration, samples were drawn at 10-min intervals from 120 to 180 min for the determination of basal leucine and a-ketoisocaproic acid (a-KIC) specific activities, as well as hormone and substrate concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Expired air samples were collected at 15-min intervals and bubbled through a CO2 trapping solution (hyamine hydroxide/absolute ethanol/0. 1% phenolphthalein, 3:5:1) as described previously (4,19). The solution was titrated to trap 1 mmol CO2 per 3 ml of solution.…”
Section: Introductionmentioning
confidence: 99%
“…where V CO 2 is the rate of CO 2 production (micromoles per kilogram per hour), 13 CO 2 MPE is the 13 C enrichment of expired CO 2 at steady state, and 0.8 is a constant representing the fractional recovery of 13 CO 2 obtained during 13 Cbicarbonate infusions in adults and newborns that corrects for the loss of the 13 C label (28,29). From the above, NOD leuc and RP leuc can then be determined using Equation 1 above.…”
mentioning
confidence: 99%